Rural Livelihood Vulnerability and Resilience: a Typology Drawn from Case Studies of Small-Scale Farmers and Fishermen in Indonesia - Dharmawan, Arya Hadi; Nissa, Zulfa Nur Auliatun (Sodality: Jurnal Sosiologi Pedesaan, 2020)
Various studies on rural household livelihood systems have been carried out in Indonesia to explain the level of household livelihood vulnerability in both farming and fishing communities. The livelihood of small-scale farmers and fishermen is usually vulnerable due to climate and non-climate pressure. This desk study compares the results of studies on livelihood vulnerability from various theses, dissertations and scientific journal articles with a similar topic of study. A case study analysis is used to figure out a comparative picture of small-scale farmers and fishermen households in responding to the pressure as well as making adaptive actions to survive. The weakness of this study is that the conclusion cannot provide evidences as a basis for deriving generalization. Rather it only provides an initial description of the socioeconomic responses as shown by small-scale farmers and fishermen in reacting to ecological pressures. This study comes up with a typology of pressure faced by small-scale farmers and fishermen households. There are four types of stressor that are identified, i.e., climate variability, capital farm expansion, rural-infrastructure development, and economic actorcompetitions. In responding to livelihood vulnerability, most of small-scale farmers and fishermen build their resiliency by using resources under the controlled household system while others use external sources.